1985
DOI: 10.1111/j.1745-4557.1985.tb00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Vitamins in Fresh and Frozen Broccoli Prepared by Different Cooking Methods

Abstract: Fresh and frozen broccoli were analyzed for retention of ascorbic acid, riboflavin and thiamine by semi-automated fluorometry before and after steaming, boiling or microwave cooking for 5 min. Retention of vitamins in general was higher for fresh than for frozen broccoli. Steamed fresh broccoli retained most ascorbic acid, riboflavin, and thiamine. Boiled fresh samples retained least riboflavin and ascorbic acid and microwaved samples, the least thiamine. In frozen broccoli, micro waved samples retained most a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…Previous studies have shown that boiling and microwaving caused a great loss of vitamin C (López-Berenguer et al, 2007;Sikora et al, 2008;Vallejo et al, 2002). Our study also shows that boiling and stir-frying/boiling caused a dramatic loss Hudson et al(1985) and Vallejo et al (2002) reported that steaming caused less loss of vitamin C than boiling and microwaving, which is consistent with our study. Stir-frying caused a considerable loss of vitamin C (16%), however, much less than stir-frying/boiling and boiling (38% and 33%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that boiling and microwaving caused a great loss of vitamin C (López-Berenguer et al, 2007;Sikora et al, 2008;Vallejo et al, 2002). Our study also shows that boiling and stir-frying/boiling caused a dramatic loss Hudson et al(1985) and Vallejo et al (2002) reported that steaming caused less loss of vitamin C than boiling and microwaving, which is consistent with our study. Stir-frying caused a considerable loss of vitamin C (16%), however, much less than stir-frying/boiling and boiling (38% and 33%, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…A few controversial data on the vitamin C retention in cooked broccoli are available in the scientific literature. Among the different cooking methods considered, higher vitamin C losses have always been recorded with the boiling procedure, as in our case (Hudson and others 1985; Vallejo and others 2002; Verkerk and others 2004; Zang and others 2004). Moreover, in our experimental conditions, microwave cooked and fresh broccoli showed similar vitamin C content ( P < 0.05), as also reported by Howard and others (1999), and an optimal retention of this moiety was also achieved using pressure and pressure/microwave cooking.…”
Section: Resultssupporting
confidence: 58%
“…Moreover, in our experimental conditions, microwave cooked and fresh broccoli showed similar vitamin C content ( P < 0.05), as also reported by Howard and others (1999), and an optimal retention of this moiety was also achieved using pressure and pressure/microwave cooking. On the other hand, Hudson and others (1985) and Vallejo and others (2002) reported that steam cooking affected the vitamin C content less than boiling and microwave cooking, while Zhang and others (2004) reported that the content of ascorbic acid dramatically decreased (> 60%) during both boiling and microwave cooking. Such discrepancies in vitamin C retention may be due to differences in the experimental cooking conditions, making impossible any reliable comparison among the cooking systems utilized by the different authors and those utilized in the present study.…”
Section: Resultsmentioning
confidence: 98%
“…Other researchers (Marbesor and Baldwin 1979;Chung et al 1981) have reported that vitamin C retention in peas cooked by microwave boiling was higher than in peas cooked by conventional methods. Hudson et al (1985) found that vitamin C retention was slightly higher in broccoli cooked by steaming than by microwaving (content of 77 mg/lOO g vs. 73 mg/100 g). Their microwaved and steamed samples were described as being firm to slightly undercooked; whereas, samples in the present study were cooked to the same tenderness as quantitated using a Shear Press.…”
Section: Resultsmentioning
confidence: 94%
“…Warthesen et al (1984) found that boiled vegetables generally retained significantly less vitamin C with no differences found among steaming, pressure cooking, and microwaving. Hudson et al (1985) also reported that boiled fresh broccoli retained less ascorbic acid, riboflavin, and thiamin than did broccoli cooked by steaming or microwave methods. Lane et al (1984) studied ascorbic acid retention in five vegetables blanched by microwave and conventional methods.…”
Section: Introductionmentioning
confidence: 93%